The Solutions to Discrimination in the Teaching Process - Ochilova Zarina Otabek qizi; Usmonova Roziya (Periodica Journal, 2023)
This article widely provides imminent solutions to discrimination in the teaching process through concrete explanations, such as creating a discrimination-free environment as well as abolishing the concept of inequality in the teaching process by creating new policies in the environment of the school and the changing mindset of learners who are discriminated
Keywords: solutions; new policy; discrimination free-environment; learners